Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00359-008-0340-4
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-dependent oscillations and evoked potentials in chinchilla auditory cortex

Abstract: Besides the intensity and frequency of an auditory stimulus, the length of time that precedes the stimulation is an important factor that determines the magnitude of early evoked neural responses in the auditory cortex. Here we used chinchillas to demonstrate that the length of the silent period before the presentation of an auditory stimulus is a critical factor that modifies late oscillatory responses in the auditory cortex. We used tetrodes to record local-field potential (LFP) signals from the left auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
3
0
3
Order By: Relevance
“…The present data are consistent with previous analyses of evoked and induced responses in the auditory system with the similar structure of time-frequency responses ( Delano et al , 2008 ; Steinschneider et al , 2008 ; Nourski et al , 2014 ). While auditory evoked and induced response has been well described in normal hearing subjects ( Tallon-Baudry and Bertrand, 1999 ; Trautner et al , 2006 ; Fujioka et al , 2009 ; Sedley et al , 2016 ) and observed also in postlingual cochlear implant users ( Agrawal et al , 2013 ; Senkowski et al , 2014 ), consequences of congenital deafness on this activity have remained unknown so far.…”
Section: Discussionsupporting
confidence: 92%
“…The present data are consistent with previous analyses of evoked and induced responses in the auditory system with the similar structure of time-frequency responses ( Delano et al , 2008 ; Steinschneider et al , 2008 ; Nourski et al , 2014 ). While auditory evoked and induced response has been well described in normal hearing subjects ( Tallon-Baudry and Bertrand, 1999 ; Trautner et al , 2006 ; Fujioka et al , 2009 ; Sedley et al , 2016 ) and observed also in postlingual cochlear implant users ( Agrawal et al , 2013 ; Senkowski et al , 2014 ), consequences of congenital deafness on this activity have remained unknown so far.…”
Section: Discussionsupporting
confidence: 92%
“…ÓLeary et al, 2023). From animal studies, it is known that the evoked potential analysis methods can eliminate important information from the single-trial frequency domain that is not time-locked to the synchronizing stimuli (Delano et al, 2008; Yusuf et al, 2017). In our experiments, we found that the cochlear microphonic responses (to the 0.5 and 2 kHz stimuli) of the same data were larger when evaluated with evoked methods than with induced methods.…”
Section: Induced Versus Evoked Analyses In Electrocochleographymentioning
confidence: 99%
“…Estudios en modelos de roedores (ratas y chinchillas) han mostrado la presencia de oscilaciones de baja frecuencia en la corteza auditiva (bandas theta, alfa y beta [< 20 Hz]), que aparecen luego de periodos de silencio y que disminuyen la amplitud de las respuestas a estímulos auditivos [33][34][35] (Figura 3). Este tipo de respuestas cerebrales amplifica la primera respuesta a un estímulo auditivo que rompe el estado de silencio.…”
Section: Oscilaciones Cerebrales En Respuesta Al Silenciounclassified
“…Estos ejem- Estímulos auditivos no precedidos de silencios prolongados provocan respuestas evocadas en la corteza auditiva sin oscilaciones posteriores (imagen inferior). Figura modificada de Délano y cols., 2008 33 .…”
Section: Tinnitus Y Respuestas Al Silenciounclassified